Trajetórias em transformação: compreensões de taxistas sobre sua atividade laboral em meio à plataformização do trabalho - Vasco, Antonio da Silva (2023)
This dissertation seeks, through the exposition of two complementary articles, to delve into the recent transformations in the work process of taxi drivers, specifically aiming to reflect on the relationships between such changes and the emergence of ride-hailing companies. The theoretical perspective that guides the analyses in this study is Social Psychology of Work. The first article, which consists of a metasynthesis, analyzes the transformations in the work of taxi drivers, their implications, and the need for studies in the field of Social Psychology of Work, based on the academic productions found in the scientific literature. In this metasynthesis, four phases were developed: exploration, refinement, description, and analysis. The analysis stage provided the construction of new understandings about the phenomenon, considering the changes brought about by new technologies and their impact on the labor precarization of taxi drivers. The second article presents the results of an empirical research and presents elements of the daily lives of Uberlândia taxi drivers, as well as their understandings about work after the emergence of ride-hailing companies. This research was carried out through semi-directed interviews, whose thematic content analysis revealed seven main categories related to the work of the participating taxi drivers, addressing everything from the process of becoming a taxi driver to perceptions about the influence of ride-hailing companies, regulatory disparities, similarities and differences between the work of these two professional categories, and the coping strategies used by taxi drivers to deal with the changes observed in their work process following the entry of ride-hailing companies into the market.